2020
DOI: 10.1093/annweh/wxaa082
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Heat Stress and Practical Cooling Solutions for Healthcare and Industry Workers During the COVID-19 Pandemic

Abstract: Treatment and management of severe acute respiratory syndrome coronavirus-2, which causes coronavirus disease (COVID-19), requires increased adoption of personal protective equipment (PPE) to be worn by workers in healthcare and industry. In warm occupational settings, the added burden of PPE threatens worker health and productivity, a major lesson learned during the West-African Ebola outbreak which ultimately constrained disease control. In this paper, we comment on the link between COVID-19 PPE and occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 53 publications
1
37
0
2
Order By: Relevance
“…The discrepancy between our perceptual heat strain results and those of the online survey in the UK may be due to differences in PPE wear time, as ~73% of health care personnel in the UK have work bouts longer than four hours compared to ~2.5 hours in our study population. Besides, the environmental conditions in healthcare settings in the UK, especially in old buildings, are demonstrated to be more severe with higher ambient air temperatures (24-29°C)23 compared to our study (~23°C).Physiological heat strainThe link between PPE use and physiological heat strain in occupational work is well established24 . The high evaporative resistance of PPE materials markedly limits the heat exchange with the environment through convection and evaporation of sweat[1][2][3] , causing T gi to increase in proportion to working intensity.…”
mentioning
confidence: 37%
“…The discrepancy between our perceptual heat strain results and those of the online survey in the UK may be due to differences in PPE wear time, as ~73% of health care personnel in the UK have work bouts longer than four hours compared to ~2.5 hours in our study population. Besides, the environmental conditions in healthcare settings in the UK, especially in old buildings, are demonstrated to be more severe with higher ambient air temperatures (24-29°C)23 compared to our study (~23°C).Physiological heat strainThe link between PPE use and physiological heat strain in occupational work is well established24 . The high evaporative resistance of PPE materials markedly limits the heat exchange with the environment through convection and evaporation of sweat[1][2][3] , causing T gi to increase in proportion to working intensity.…”
mentioning
confidence: 37%
“…Offering opportunities and implementing the right policies appears important also because in our study, the overwhelming majority of nurses and healthcare workers were not able to effectively deploy countermeasures against heat stress on their own. As two thirds of study participants (67%) reported that they drank more water, it may make sense for healthcare centres to offer extra water or ice slurries, as has been recommended in one recent study [9]. Offering cold water temperatures has both a cooling effect and increases the likelihood that nurses take up more fluid during their shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Offering cold water temperatures has both a cooling effect and increases the likelihood that nurses take up more fluid during their shifts. Moreover, training staff to frequently drink water will not only help during heat waves but will in general work against another common danger in the workplace - dehydration [9]. One possibility to incorporate this into the nursing shifts would be for the employer or hospital to inform nurses of this option and offering boxes filled with ice for everyone to use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Western countries already have adopted and implemented heat health action plans ( Bittner et al, 2014 ; Casanueva et al, 2019 ). With the Covid-19 pandemic, is it necessary to adapt these plans to address the conflicting advice for protection against Covid-19 and for heat management ( Daanen et al, 2020 ; Foster et al, 2020 ; Lee et al, 2020 ; Martinez et al, 2020 ; Morabito et al, 2020 ). Information addressing this issue was compiled and the first recommendations have been published on national and international levels (Global Heat Health Information Network (GHHIN), 2020).…”
Section: Introductionmentioning
confidence: 99%